THE IMPORTANCE OF NARRATIVES IN SPIRITUAL EDUCATION OF PRIMARY CLASS STUDENTS - Mamatsoliyeva Xurshida Xamdamovna, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article describes the concept of language corpus, corpus annotation and morphological classification, recognized as one of the important factors in the future development of the Uzbek language.